First report of Blastocystis in giant pandas, red pandas, and various bird species in Sichuan province, southwestern China - Lei Deng; Jing-Xin Yao; Hai-Feng Liu; Zi-Yao Zhou; Yi-Jun Chai; Wu-You Wang; Zhi-Jun Zhong; Jun-Liang Deng; Zhi-Hua Ren; Hua-Lin Fu; Xia Yan; Chan-Juan Yue; et al. (International Journal for Parasitology: Parasites and Wildlife, 2019)
Blastocystis is a common enteric protist that colonizes humans and a wide range of animals. Although some studies have reported incidences of Blastocystis in humans and animals in China, there is no information available on the prevalence of Blastocystis in giant pandas, red pandas, or bird species. The aims of the present study were to determine the prevalence, subtype distribution, and genetic characterizations of Blastocystis in these animals in a captive situation in southwestern China, as well as assess the zoonotic potential of Blastocystis isolates. A total of 168 fecal specimens, including 81 from giant pandas, 23 from red pandas, 38 from black swans, 11 from ruddy shelducks, and 15 from green peafowl were collected at the Chengdu Research Base of Giant Panda Breeding in Sichuan province. The overall minimum prevalence of Blastocystis was 11.3% (19/168) based on PCR amplification of the barcode region of the SSU rRNA gene. The highest prevalence of Blastocystis was observed in ruddy shelduck (18.2%) and the lowest was found in green peafowl (6.7%). The prevalence of Blastocystis in giant pandas >5.5 years of age was higher than that in younger giant pandas. Two potentially zoonotic subtypes (ST1 and ST8) were identified, and ST1 (n = 12) was found to be more prevalent than ST8 (n = 7). To the best of our knowledge, this is the first report of the prevalence and subtypes of Blastocystis in giant pandas, red pandas, and bird species in China. The findings of this study will improve our understanding of the genetic diversity and public health potential of Blastocystis. Keywords: Blastocystis, Pandas, Genetic diversity, Zoonotic potential, China